Application of Rhizobacteria to Control Phytophthora capsici Disease Causes Stem Base Rot and Increase Growth of Pepper Seedlings In-Vivo - La Mudi; Zainal Abidin; Riama Rita Manullang; Sopian Agus; Helmi Ahmad Gyn Nandi; Tasya Valentina Putri; Gusti Ayu Kade Sutariati (International Journal on Food, Agriculture and Natural Resources, 2024)
One of the obstacles to pepper production is the high intensity of plant disease attacks. One of them is stem rot disease caused by the fungus Phytophthora capsici. Therefore, appropriate technology is needed that can control disease and at the same time increase plant growth by using rhizobacteria which are environmentally friendly, and can produce growth hormones, dissolve phosphate, and fix nitrogen. This research aims to obtain rhizobacteria isolates that can control the pathogen P. capsici which causes root rot disease, while also being able to increase plant growth. This research was carried out at the Agronomy Laboratory of the Plantation Plant Cultivation Study Program, Samarinda State Agricultural Polytechnic. The research used a completely randomized design consisting of 4 treatments with 4 replications to obtain 16 experimental units. Variables observed included the latent period, disease incidence and severity, increase in plant height, number of leaves, and stem diameter. The resulting data was analyzed using analysis of variance (ANOVA). The results of the analysis showing a real effect were followed by the Least Significant Difference test (BNT)α=0.05. The results of the research showed that the application of a combination of rhizobacteria was able to overcome stem rot disease and at the same time increased the growth of pepper plant seedlings. The combination of rhizobacteria isolates P01 + TA2 treatment can reduce the latent period of disease to 12.00 days compared to 5.50 days without rhizobacteria, the disease incidence rate is 6.25% with a severity level of 2.50%, lower than without treatment (control) at 37.50 % (disease incidence) and 47.50% (disease severity). Apart from that, the combination of rhizobacteria isolates P01 + TA2 was able to increase the growth of pepper plant seeds as shown by observing the increase in plant height, number of leaves, and stem diameter